A survey on malware propagation, analysis, and detection - Damshenas, Mohsen; Dehghantanha, Ali; Mahmod, Ramlan (The Society of Digital Information and Wireless Communications, 2013)
Lately, a new kind of war takes place between the security community and malicious software developers, the security specialists use all possible techniques, methods and strategies to stop and remove the threats while the malware developers utilize new types of malwares that bypass implemented security features. In this study we closely looked into malware, to understand the definition, types, propagation of malware, and detecting/defending mechanisms in order to contribute to the process of protection and security enhancement.